Pengaruh Profitabilitas, Struktur Modal, Tanggungjawab Sosial Perusahaan, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Yoseph Kowawin; Alfonsus Rodriques Suninono (Universitas 17 Agustus 1945 Jakarta, 2022)
This study aims to examine the effect of profitability, capital structure, corporate social responsibility and firm size on firm value. The independent variables used are profitability, capital structure, corporate social responsibility and company size. While the dependent variable used is the value of the company. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. Samples were collected using purposive sampling method. A total of 20 companies were determined as samples. The analytical method of this study uses panel data regression. The results of this study indicate that profitability, capital structure and corporate social responsibility have a negative and insignificant effect on firm value. Meanwhile, firm size has a positive and significant effect on firm value.